Modeling Multi-Factor Coupled Pressure Fluctuations in EMU Trains under Extreme Tunnel Conditions - Miao Zou; Chunjun Chen; Lu Yang (Applied Sciences)
As an electric multiple unit (EMU) train passes through an extreme tunnel characterized by high altitude, steep gradient, and extended lengths, the pressure waves generated by the train–tunnel aerodynamic coupling combine with the baseline pressure variations within the tunnel. This interaction results in rapid fluctuations and extreme external pressure with higher amplitudes, which are transmitted into the carriage, causing pressure fluctuations that can adversely affect passenger comfort. These waves interact with multiple factors within the carriage, such as air ducts, airtight gaps, carbody deformation, oxygen supply systems, and temperature, creating a highly nonlinear internal pressure transmission system. This study first establishes a single-factor internal pressure fluctuation model. Subsequently, a multi-factor coupled internal pressure fluctuation model is constructed based on the ideal gas polytropic process assumption and the law of mass conservation. The model parameters are corrected and the model’s effectiveness and accuracy are validated using experimental data to predict and summarize the internal pressure variation patterns of the EMU train during dynamic operation in such tunnels, ensuring safe train operation and meeting the pressure comfort requirements of passengers. Finally, to address the challenges of maintaining and regulating multi-physical variable comfort under extreme tunnel conditions, this study investigates the impact of partial oxygen pressure and temperature on pressure fluctuations and comfort. The study finds that higher oxygen pressure and temperature significantly increase internal pressure fluctuation amplitude, with the oxygen supply system contributing 18.11% and temperature 5.74% of total variation. Thus, setting appropriate standards for oxygen supply, temperature, and valve operation is crucial for mitigating internal pressure fluctuations and enhancing safety and comfort. This research provides a theoretical foundation for developing a comprehensive comfort evaluation and regulation system under harsh environments.